2021
DOI: 10.1002/jat.4164
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and inflammatory effects in human bronchial epithelial cells induced by polycyclic aromatic hydrocarbons mixture

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are the most common contaminants in the air pollutants. Inhalation exposure to PAHs could increase the risk of respiratory disease, cardiovascular disease and even cancer. However, the biotoxicity of multi‐component PAHs from atmospheric pollutants has been poorly studies. The main topic of this study was to investigate the PAHs mixture, which derived from atmospheric pollutants, induced toxic effects and inflammatory effects on human bronchial epithelial cells in vitro.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Previous studies have also revealed that PAHs can independently activate the NF-κB pathway, leading to cellular toxicity and inflammation. 46,47 Additionally, our previous studies have indicated that Cl-PAHs induce immune toxicity by disrupting amino acid metabolism without activating AhR. 12 These findings underscore the complexity of the toxic effects of PAHs/Cl-Ants, suggesting the involvement of multiple pathways and mechanisms beyond AhR activation.…”
Section: Revelation Of Molecular Mechanisms and Key Immune-related Ge...mentioning
confidence: 90%
“…Previous studies have also revealed that PAHs can independently activate the NF-κB pathway, leading to cellular toxicity and inflammation. 46,47 Additionally, our previous studies have indicated that Cl-PAHs induce immune toxicity by disrupting amino acid metabolism without activating AhR. 12 These findings underscore the complexity of the toxic effects of PAHs/Cl-Ants, suggesting the involvement of multiple pathways and mechanisms beyond AhR activation.…”
Section: Revelation Of Molecular Mechanisms and Key Immune-related Ge...mentioning
confidence: 90%
“…The respiratory tract is constantly in contact with various pollutants, so PAHs tend to concentrate in bronchial epithelial cells [18]. Due to their lipophilic nature, they can easily penetrate the epithelial barrier and accumulate in adipocytes, which leads to chronic activation of the aryl hydrocarbon receptor (AhR) [19], triggering an inflammatory response.…”
Section: Introductionmentioning
confidence: 99%